STRATEGIES TO CREATE A POSITIVE CLASSROOM ENVIRONMENT IN TEACHING ENGLISH AS FOREIGN LANGUAGE (TEFL) - Maria Ramasari (LP4MK STKIP PGRI Lubuklinggau, 2015)
This article discusses about tearcher’s strategies to create a positive classroom environment in Teaching English as Foreign Language. One of the first tasks of teaching is to develop a learning environment so that students can engage in meaningful activities that support their learning. Teachers who are able to engage students in a teaching and learning process should be ready to have a plan to create a positive classroom environment for students. Creating a positive classroom environment is an important aspect of effective teaching. It is for keeping the interaction between teacher and students in teaching and learning process at classroom so that it increases students’ motivat ion to learn. Then, students are productive in and out of the classroom. By creating positive classroom environments, teachers have the opportunity in developing their ideas for better classroom environment. Furthermore, it also help to enhance and encourage students in learning English as Foreign Language. In addition, this article also describes the effects of a positive classroom environment on students’ learning English as Foreign Language.